Definition: Space-Time Interval - Tannous, Saliba (European Journal of Applied Sciences, 2024)
The concept of spacetime interval is not clearly understood or defined in modern physics. Here, I will present a clear and precise explanation and definition of the concept of spacetime interval. This research is based on a different representation of spacetime, Additionally, we will introduce and demonstrate a new physical theory that will make all of modern physics more logical and easier to understand.